Religiosity of Women with Cervical Cancer in RSUD Dr. Moewardi Surakarta - Sulastri Sulastri; Octavia Dwi Ningrum; Ni'mah Mufidah (STRADA : Jurnal Ilmiah Kesehatan, 2021)
One of the important needs that patients want is to fulfill religious needs to improve their quality of life. Religious behavior is action(s) taken by a person to be able to get peace of mind for example by doing salah (Muslim prayer), dhikr, praying, and reciting Qur’an. Religious aspects must be concerned in the treatment especially for patients with terminal cases. This study aims to determine the image of religiosity and family religious support among the women with cervical cancer who were treated at RSUD Dr. Moewardi Surakarta. This quantitative research using descriptive method, involving 90 samples selected through purposive sampling; data were collected using questionnaires and processed using univariate analysis and central tendency. The results of this study indicate that the religious image of cervical cancer patients shows that the most religious activity done is dhikr (97.8%); and family religious support among the patients is not sufficiently good (64.4%).